PREVALENCE OF TOXOCARA CANIS WORM INFECTION OF KINTAMANI PUPPIES IN BANGLI REGENCY BALI - Widiasih, Ni Nyoman; Dwinata, I Made; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2023)
The kintamani dog is one of the original Indonesian breed dogs that have a lot of fans. This dog comes from the mountainous area of Sukawana Village, Kintamani District, Bali. Toxocariosis is one of the most common diseases infecting puppies. The more interest of this puppies, it affect the way they are kept, which sometimes causes diseases caused by bacteria, viruses  and parasites. One of the is T. canis worm can cause inflammation and edema in the liver and lungs puppies. This study aims to determine the prevalence of T. canis infection in kintamani puppies and their relationship with risk factors for dog age. This study is an observational study with a cross-sectional approach. The total sample of this study amounted to 100 samples of feces of kintamani puppies, examined by flotation concentration method using saturated salt solution. The research data is presented descriptively and to determine the relationship between age and prevalence, the chi-square analysis is used. The results showed that the prevalence of T. canis infection in kintamani puppies was 79% (79/100). The results of the study were based on age group: the prevalence of kintamani puppies at 1 month old was 62.5% (15/24), at 2 months the prevalence was 90.3% (28/31), and at 3 months the prevalence was 80.0% (36/45). The results of the chi-square test analysis showed that there was a significant relationship between age risk factors (P<0.05) and the prevalence of T . canis infection. Regular administration of deworming drugs to puppies and pregnant mother dogs 1 to 2 weeks before birth to prevent and reduce transmission of T . canis worm infection through prenatal and transmamari.